Gender-Based Disparities in Technical Education Assessment and Certification Outcomes Across Philippine Regions: A Regional Perspective - Flores, Jomar; Sambaan, Rico; Dullente, Jenmarie; Jamilo, Jolliven; Mahinay, Ray Butch (Journal of Interdisciplinary Perspectives, 2025)
This study investigates gender-based disparities in assessment and certification outcomes within the Philippine technical vocational education system by analyzing 3,030,892 candidates—1,609,060 males and 1,421,832 females—across 17 regions and the Central Office in the year 2024. While national data suggest general gender parity in Technical and Vocational Education and Training (TVET), regional-level disparities remain underexplored. Using a descriptive-comparative quantitative design and secondary data from publicly available reports, the study assessed regional certification rates and calculated gender gaps. Results revealed that the National Capital Region recorded the highest certification rates for both males (97.48%) and females (98.01%). At the same time, Region X exhibited the widest gender gap at -18.81%, with males significantly underperforming compared to females. Region I demonstrated near gender parity with only a 0.23% difference. These findings underscore the uneven distribution of TVET success across areas, shaped by socio-economic, institutional, and gender-specific factors. The study highlights the need for localized, gender-responsive interventions, including improved training access, targeted support for underperforming groups, and stronger regional implementation of national TVET equity policies to ensure inclusive skills development across the country.